Evaluation of Community Participation in Restoration Efforts Following the Merapi Volcano Eruptions in Muntilan, Magelang - Istiyanto, S. Bekti; Tri Wijayanti, Yani (KnE Social Sciences, 2023)
Disasters due to the frequent eruptions of Mount Merapi have attracted great attention. For example, from the beginning of 2020 to June 21, 2020, 10 eruptions brought panic to the community. To avoid the unpreparedness of the community when a disaster occurs, the government and the private sector have provided programs to the victims. The program is running at the optimal planning and implication stage. However, in the next stage, programs that involve the active participation of affected communities run at a low level. This study uses a qualitative descriptive method to produce in-depth data from local government informants and community leaders who are victims of disasters and develop post-disaster reconstruction programs. Data collection techniques included in-depth interviews, observation, and documentation of appropriate and required data. The results of this study include, in Muntilan District, Magelang Regency, there has been a community recovery program in the form of post-disaster emergency assistance, as well as other economic recovery programs to restore life to normal. Initially, the handling of the community’s economic recovery program did not go as expected. Many aids were given directly to the community but were not useful due to obstacles in the field; The results of the evaluation of the level of community participation in Magelang Regency, in general, can be classified as very low in post-disaster development programs. Keywords: eruption, aid program, normal life, participation